Influence of filler treatment on the behavior of blast furnace slag filled polypropylene compounds. Issue 31 (23rd April 2018) - Mostafa, A.; Lucyshyn, T.; Holzer, C.; Flachberger, H.; Oefner, W.; Riess, G.; Fritz, B.
ABSTRACT: Blast furnace slag (BFS) is a byproduct of the blast furnace in iron industry. Due to its composition and structure, BFS is suggested as a promising functional filler that can potentially improve the property profile of polypropylene. To overcome the lack of compatibility between BFS and polypropylene (PP), two coupling agents, vinylethoxysiloxane homopolymer silicon and methacryloxypropyltrimethoxysilane, are utilized for treating the BFS surface. The influence of each coupling agent on the BFS–PP compound properties is investigated in this work. It is observed that both coupling agents equally increase the complex shear viscosity and thermal conductivity of the modified BFS compounds by 10% and 12%, respectively, compared to their unmodified counterparts. The degree of crystallinity of the modified compounds also increased by more than 25%. While the tensile stiffness and yield strength levels are found to be comparable for all compounds, the strain at break of some modified BFS compounds is doubled. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46535. Abstract :